Redefining health priorities: Sub-Saharan Africa’s new frontier in disease burden - Zerfu, Taddese Alemu; Tareke, Amare A.; Biadgilign, Sibhatu (International Society of Global Health, 2024)
Recent Lancet Global Burden of Disease Study projections highlight a significant transformation in sub-Saharan Africa’s (SSA) health landscape by 2050 [1]. Although global age-standardised disease burden and life expectancy are anticipated to improve, SSA will move from primarily impacted by communicable, maternal, neonatal, and nutritional diseases (CMNNs) to an increasing prevalence of non-communicable diseases (NCDs). This evolving scenario requires urgent modifications in public health strategies to tackle both ongoing and emerging health challenges.